2017
DOI: 10.1038/s41598-017-13857-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mazEF/pemIK family toxin-antitoxin loci and their distribution in the Staphylococcus genus

Abstract: The versatile roles of toxin-antitoxin (TA) systems in bacterial physiology and pathogenesis have been investigated for more than three decades. Diverse TA loci in Bacteria and Archaea have been identified in genome-wide studies. The advent of massive parallel sequencing has substantially expanded the number of known bacterial genomic sequences over the last 5 years. In staphylococci, this has translated into an impressive increase from a few tens to a several thousands of available genomes, which has allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 73 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…In fact, the role of TA systems, in the context of stable genetic material maintenance in bacteria, is well-documented (Tsuchimoto et al, 1988; Sobecky et al, 1996; del Solar et al, 1998; Van Melderen and Saavedra De Bast, 2009; Bukowski et al, 2011, 2013). A number of recent reports point out their possible importance for drug resistance dissemination as well, for instance among enterococci (Moritz and Hergenrother, 2007; Rosvoll et al, 2010; Bukowski et al, 2017). However, it still seems that their role in this phenomenon has yet not received due attention.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the role of TA systems, in the context of stable genetic material maintenance in bacteria, is well-documented (Tsuchimoto et al, 1988; Sobecky et al, 1996; del Solar et al, 1998; Van Melderen and Saavedra De Bast, 2009; Bukowski et al, 2011, 2013). A number of recent reports point out their possible importance for drug resistance dissemination as well, for instance among enterococci (Moritz and Hergenrother, 2007; Rosvoll et al, 2010; Bukowski et al, 2017). However, it still seems that their role in this phenomenon has yet not received due attention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, comparative studies of the distribution of TA systems in mycobacteria have demonstrated the variability of TA loci between different M. tuberculosis lineages, and led to the discovery of putative novel TA systems [ 42 , 43 ]. Similarly, the body of knowledge about the TA systems of S. aureus [ 44 ] was recently expanded by several studies providing insights into the association between the TA systems landscape and strain phenotypes [ 45 , 46 , 47 , 48 ]. A recent in-depth analysis of the diversity and distribution of type II and type IV TA systems in the genomes of K. pneumoniae species complex identified several novel toxins and demonstrated the co-occurrence of TA loci and clinically relevant genes [ 49 ].…”
Section: Type II Ta Systems In Pathogenic Bacteriamentioning
confidence: 99%
“…The TA system, which typically comprises a bicistronic operon encoding a stable protein 'toxin' and a labile protein 'antitoxin', have received much attention because of their vital roles in bacterial physiology [5]. As yet, six types of TA systems have been identified based on their mechanism of action and their nature of the antitoxin (RNA or protein), while the toxin is in all of them a protein [6].…”
Section: Introductionmentioning
confidence: 99%
“…The toxins and antitoxins of all considered bacterial type II TA systems are proteins and are the most prevalent and best-described TAs [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation